Photocatalytic performance of cuttle fish bone nano-membrane adsorbents for water remediation - Peeyush Phogat; Shreya; Ranjana Jha; Sukhvir Singh (Results in Surfaces and Interfaces)
This study explores the effectiveness of cuttlefish bone (CFB) as a photocatalyst for wastewater treatment, focusing on its ability to degrade organic pollutants, specifically malachite green dye. The highly porous structure of CFB, confirmed by BET analysis, enhances its capacity for efficient dye removal. Morphological analysis revealed that the material's porosity plays a crucial role in adsorbing dye molecules onto the surface, while zeta potential and thermogravimetric analysis (TGA) confirmed its stability and minimal agglomeration in aqueous solutions. X-ray diffraction (XRD) analysis identified calcium carbonate (CaCO3) as the primary phase in CFB, while elemental analysis indicated significant carbon content, contributing to its photocatalytic activity. UV–Vis spectroscopy was employed to investigate the material's photocatalytic properties, and concentration and pH studies were conducted to understand the dye degradation mechanism. CFB demonstrated a high degradation efficiency of malachite green dye, achieving a 92% reduction within 120 min under optimized conditions. This was further supported by scavenger tests that identified key active species involved in the photocatalytic process, including hydroxyl radicals (OH∗) and superoxide ions (∗O2−). Overall, the study demonstrates that CFB, with its high surface area, thermal stability, and eco-friendly nature, is a highly effective and sustainable material for photocatalytic water treatment, offering significant potential for wastewater remediation.